SIGNIFICANCE OF DIET AND DIETARY SUPPLEMENTS IN GOUT - A E Il'ina; V G Barskova; A E Ilyina; V G Barskova (Современная ревматология, 2008)
The paper discusses a role of a diet and therapy with the herbal complex Urisan in patients with gout. It is noted that the agent based on herbal components may be used in addition to drug therapy and diet in seasonal hyperuricuria, hyperuricemia observed after heavy strenuous and athletic activity, meat overeating, and alcohol abuse. Urisan may be recommended in subsiding gouty inflammation as a bridge to the use of allopurinol.